The Policy For Handling Criminal Acts Of Insult/Hate Speech Or Damage Through Internet - Didik Sudarmadi; Jawade Hafidz (Universitas Islam Sultan Agung, 2021)
The purpose of this study is to find out and analyze the legal policy of the Information and Electronic Transactions Law (ITE) on the handling of criminal acts of defamation via the internet in Indonesia, to find out the obstacles to handling it. This study uses a sociological juridical approach, with analytical descriptive research methods. The results of the study conclude that crime prevention efforts need to be pursued with a policy approach, in the sense that there is an integration between criminal politics and social politics and there is an integration between penal and non-penal crime prevention efforts. The obstacle faced by law enforcement officers today is how to capture cybercrime perpetrators in relation to the provisions of the applicable criminal law. Law enforcement officers are faced with difficulties in determining the qualifications of crimes given the difficulty of finding evidence. As well as solutions for resolving criminal defamation cases through electronic social media at the Indonesian Police in two ways, namely through penal facilities (repressive activities after the occurrence of a crime) and non-penal means, in the form of counseling for preventive actions.